Insertional Torque and Pullout Strength of Pedicle Screws with or without Repositioning: A Porcine Study. (August 2014) - Tan, Chun Ee; Fok, Margaret Woon Man; Luk, Keith Dip Kei; Cheung, Kenneth Man Chee
Purpose: To evaluate the insertion torque and pullout strength of pedicle screws with or without repositioning. Methods: 20 fresh porcine lumbar vertebrae of similar size were used. The entry point was at the site just lateral and distal to the superior facet joint of the vertebra, and to a depth of 35 mm. A 6.2-mm-diameter, 35-mm-long pedicle screw was inserted parallel to the superior end plate on one side as control. On the other side, an identical screw was first inserted 10° caudal to the superior end plate, and then repositioned parallel to the superior end plate. The insertional torque and pullout strength were measured. Results: Three of the specimens were excluded owing to pedicle fractures during the pullout test. Repositioned pedicle screws were significantly weaker than controls in terms of the maximum insertional torque (3.20±0.28 vs. 2.04±0.28 Nm, 36% difference, p±0.01) and pullout strength (1664±378 vs. 1391±295 N, p±0.01). Conclusion: Repositioning pedicle screws should be avoided, especially when the pedicle wall is breached. If repositioning is deemed necessary, augmentation with polymethyl methacrylate or a screw with a larger diameter should be considered.